Dampak pandemi covid-19 pada pembelajaran penjasorkes Smp di Kota Blora - Anis Aisyah Nur Aini; Husnul Hadi; Agus Wiyanto (YLPK Mahardhika, 2021)
The impact of the outbreak of Covid-19 is extraordinary, especially in the field of education. Students must be able to participate in online-based learning because it is not possible to study in schools which are still a threat to students as a place for virus transmission. The COVID-19 pandemic has brought concerns to the implementation of education and learning in junior high schools, the most severe conditions experienced by schools that are far from urban areas with limited internet access and infrastructure. The method used in this study is a qualitative research method. Qualitative research does not use a population and sample approach. Testing the credibility of the data or trust in the results of qualitative research, among others, is carried out by extending observations, increasing persistence in research, triangulation, discussions with colleagues, negative case analysis, and member checking. Data analysis carried out is data reduction, data display, and conclusion drawing/verification. From the results of the research, all teachers explained that this pandemic had a positive impact on the giving and receiving of written materials. This happened because there was quite a lot of time in the provision of material. Because the material could be conveyed to students quite well, the students' written test scores increased significantly. the negative impact is that the child cannot practice optimally. Because there is one school that does not practice at all, namely SMP Muhammadiyah 1 Blora. The teacher does not allow students to practice because of many considerations. Meanwhile, SMP N 5 Blora, SMP N 7 Blora and SMP Plus Insan Gemilang continue to apply the practice for their students, but only on certain materials that are not classified as dangerous. Based on the results of the study and the data obtained by the researchers, it can be concluded that this study obtained the results that the covid-19 pandemic had an impact on physical education learning in Blora City. These impacts include negative and positive impacts for teachers, students and parents.